2021
DOI: 10.1007/s00382-020-05588-6
|View full text |Cite
|
Sign up to set email alerts
|

The differing role of weather systems in southern Australian rainfall between 1979–1996 and 1997–2015

Abstract: Most of the rainfall in southern Australia is associated with cyclones, cold fronts, and thunderstorms, and cases when these weather systems co-occur are particularly likely to cause extreme rainfall. Rainfall declines in some parts of southern Australia during the cool half of the year in recent decades have previously been attributed to decreases in the rainfall from fronts and/or cyclones, while thunderstorm-related rainfall has been observed to increase, particularly in the warm half of the year. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 52 publications
6
45
0
1
Order By: Relevance
“…This decline is not related to any change in front frequency (Figure 2b) but due to a decrease in the average rainfall intensity calculated across all fronts. This decrease in intensity is due to a decrease in the likelihood that a front will produce measurable rain in these latitudes (Figure 2d) and a corresponding increase in dry fronts, consistent with Pepler et al (2021); for fronts that produce rainfall, the average rainfall intensity has not changed (Figure 2e). 165…”
Section: Changes In Frontal Rainfall 130supporting
confidence: 68%
See 2 more Smart Citations
“…This decline is not related to any change in front frequency (Figure 2b) but due to a decrease in the average rainfall intensity calculated across all fronts. This decrease in intensity is due to a decrease in the likelihood that a front will produce measurable rain in these latitudes (Figure 2d) and a corresponding increase in dry fronts, consistent with Pepler et al (2021); for fronts that produce rainfall, the average rainfall intensity has not changed (Figure 2e). 165…”
Section: Changes In Frontal Rainfall 130supporting
confidence: 68%
“…However, these studies typically found that this decrease in rainfall was not due to changes in the frequency of fronts. Indeed, studies have consistently observed little change in frontal frequency over the Southern Hemisphere midlatitudes in reanalyses (Berry et al, 2011; Solman & Orlanski, 2014), although 25 some decreases have been observed in the frequency of midlatitude cyclones (Pepler et al, 2021; Pepler, 2020b). Frontal frequency in southeastern Australia has had little change over this period, despite expectations of a southward shift in fronts due to observed trends towards a positive Southern Annular mode (SAM) phase (Fogt & Marshall, 2020) and an intensification of the Southern Hemisphere storm track during winter (Chemke et al 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pepler et al. (2021) found that by comparing 1997–2015 to 1979–1996, southeast Australia has had a decrease in the frequency of rain‐producing fronts and cyclones, and an increase in the frequency of cold fronts and thunderstorms that do not produce rainfall in some regions. Thunderstorm rainfall has also increased in much of southern Australia, especially during the summer months, including an increase in rainfall where a thunderstorm environment occurs at the same time as a cyclone or front (Pepler et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant distinction between the rainfall characteristics in central, southwest, and southeast Australia. The majority of central Australia receives rainfall due to thunderstorms, while rainfall in the southwest and southeast of the country is mainly brought by fronts, cut‐off lows, east coast lows embedded within westerlies, and thunderstorms (Catto et al ., 2012; Pepler et al ., 2020; Pepler et al ., 2021). Although these systems can occur at any time of the year, they are more common in winter.…”
Section: Introductionmentioning
confidence: 99%